Evaluation of the Gene Xpert Mycobacterium tuberculosis/resistance to rifampicin assay in rapid diagnosis of tuberculosis and identification of rifampin resistance in tuberculous patients - Amal H.G. Hamed; Mona M. Ahmed; Eman R.A. Al Adawy; Rehab M.M. Fathy (Egyptian Journal of Chest Disease and Tuberculosis)
Background Since the revolutionary introduction of the Gene Xpert Mycobacterium tuberculosis/resistance to rifampicin (MTB/RIF) assay into the field of diagnostic techniques for Tuberculosis (TB), it has been gaining increasing popularity as it offers of MTB detection together with RIF–Resistance in almost two hours with high accuracy, allowing physicians to customize appropriate and accurate treatment regimens without time delay. Objective To assess the diagnostic utility of Gene Xpert in TB diagnosis and detection of RIF–Resistance in both pulmonary and extrapulmonary specimens. Methods This is a prospective, cross-sectional study in which specimens from 77 suspected pulmonary and extrapulmonary TB cases were collected and examined via three techniques: Gene Xpert, direct smear microscopy for fast bacilli (AFB) along with culture on Löwenstein–Jensen medium (the reference standard method) and drug susceptibility testing for positive cultures. Results The Xpert assay had the highest sensitivity and diagnostic accuracy in the detection of pulmonary TB (96.4%, 93.1%, respectively), with 90% specificity. Xpert assay showed much lower sensitivity and specificity in diagnosing extrapulmonary TB (71.4%, 83.3%, respectively). Moreover, Gene Xpert assay showed 100% specificity in the identification of RIF-Resistance with the highest sensitivity in pulmonary TB (90.9%). Conclusion Gene Xpert MTB/RIF showed a comparable diagnostic yield to that of conventional culture with better performance among pulmonary specimens. In addition, the assay had 100% specificity in diagnosing RIF–Resistance in pulmonary and extrapulmonary specimens.